2022
DOI: 10.1007/s40264-022-01256-2
|View full text |Cite
|
Sign up to set email alerts
|

The Food and Drug Administration’s (FDA’s) Drug Safety Surveillance During the COVID-19 Pandemic

Abstract: Introduction On 4 February, 2020, the Secretary of the Department of Health and Human Services declared a public health emergency related to coronavirus disease 2019 (COVID-19), and on 27 March, 2020 declared circumstances existed to justify the authorization of the emergency use of drug and biological products (hereafter, “drugs”) for COVID-19. At the outset of the pandemic with uncertainty relating to the virus, many drugs were being used to treat or prevent COVID-19, resulting in the US Food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Further, AE reporting probabilities may differ by medicine and severity; for instance, serious acute events are more likely to be reported than mild events with a prolonged onset. Thirdly, the data evaluated were not from recent years and thus avoided any impact COVID-19 may have had on reporting patterns [ 54 ] as well as the other datasets utilized in this study. To address concerns about generalizability, we subsequently evaluated the characteristics of reports received by FAERS in 2019 and found patterns to be largely consistent with earlier years (OSM Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Further, AE reporting probabilities may differ by medicine and severity; for instance, serious acute events are more likely to be reported than mild events with a prolonged onset. Thirdly, the data evaluated were not from recent years and thus avoided any impact COVID-19 may have had on reporting patterns [ 54 ] as well as the other datasets utilized in this study. To address concerns about generalizability, we subsequently evaluated the characteristics of reports received by FAERS in 2019 and found patterns to be largely consistent with earlier years (OSM Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that the efficacy of some mAbs against specific variants and subvariants can be variable [15]. The Food and Drug Administration (FDA) has granted emergency use authorization to a number of antibody therapies, generally in the form of a mixed cocktail of antibodies, to better target a broad spectrum of SARS-CoV-2 variants [16]. One concern about employing mAbs therapies is that the emergence of new variants, such as the Omicron, are often unaffected by their use [17–19].…”
Section: Introductionmentioning
confidence: 99%
“…Reference 8 until 6/Oct/2023, over 771 million cases and more than 6.9 million deaths worldwide have been confirmed by the WHO and over 13 billion vaccine doses have been administered 9 , 10 . This global health issue has had an impact on the utilisation of healthcare systems with a significant reduction of minor ailment consultations 11 and massive vaccination campaigns against COVID-19 12 , which may have affected the number and type of adverse events (AEs) deposited in spontaneous reporting systems (SRSs) during the pandemic period 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%